Unveiling biophysical characteristics in different triathlon race formats: a systematic review - Machado, M. L.; Assíria-Costa, L.; Santos, C. C.; Costa, M. J. (AIMS Biophysics, 2025)
Triathlon is an endurance sport growing in popularity. There are various triathlon race formats that require different types of effort. However, there is a lack of information regarding the integrated physiological and biomechanical characteristics of the different race formats. Thus, our aim of this systematic review was to synthesize the biophysical characteristics of different triathlon race formats. The methodology was conducted following PRISMA 2020 guidelines searching Web of Science, PubMed, and Scopus databases. Eligibility criteria were defined for the PICOS strategy (healthy mature triathletes, biomechanical and/or physiological assessment, continuous efforts simulating either segments of races or full races, cardiovascular demand, aero/hydrodynamic, and a technical profile). The quality index was assessed with the Downs and Black Assessment Checklist. A total of 8560 articles were screened, of which 30 satisfied the inclusion criteria, and these were grouped in short-distance race formats (n = 18) and middle-distance race formats (n = 12). Overall, studies showed a quality score of 11.86 ± 1.05 points. The biophysical profile of triathlon is influenced by multiple factors, including race distance, competitive level, segment-specific demands, and sex. Within the literature, there is a lack of analysis concerning other race formats, such as long-distance events (e.g., Ironman and Deca-Ironman), as well as new emerging race formats (e.g., Supertri, Arena Supertri (World Triathlon Championship, or T100).